The Prevalence, Impact, and Treatment of Migraine and Severe Headaches in the United States: A Review of Statistics From National Surveillance Studies. Issue 3 (7th March 2013) - Smitherman, Todd A.; Burch, Rebecca; Sheikh, Huma; Loder, Elizabeth
<x xml:space="preserve">Abstract</x> Background Four ongoing US public health surveillance studies gather information relevant to the prevalence, impact, and treatment of headache and migraine: the National Health Interview Survey, the National Health and Nutrition Examination Survey, the National Ambulatory Care Survey, and the National Hospital Ambulatory Medical Care Survey. The American Migraine Prevalence and Prevention (AMPP) study is a privately funded study that provides comparative US population‐based estimates of the prevalence and burden of migraine and chronic migraine. Objective To gather in one place and compare the most current available estimates of the US adult prevalence of headache and migraine, and the number of affected people overall and in various subgroups, and to provide estimates of headache burden and treatment patterns by examining migraine and headache as a reason for ambulatory care and emergency department (ED) visits in the United States. Methods We reviewed published analyses from available epidemiological studies identified through searches of PubMed and the National Center for Health Statistics. We aimed to identify information about migraine and headache burden, and treatment in national surveys conducted over the last decade. For each source, we selected the best available and most current estimate of migraine or headache prevalence, and selected associated measures of disability, health care use, and treatment patterns. Results Compared with a slightly higher proportion of 22.7% in the National Health and Nutrition Examination Survey, 16.6% of adults 18 or older reported having migraine or other severe headaches in the last 3 months in the 2011 National Health Interview Survey. In contrast, the AMPP study found an overall prevalence of migraine of 11.7% and probable migraine of 4.5%, for a total of 16.2%. Data from National Ambulatory Medical Care Survey/National Hospital Ambulatory Medical Care Survey showed that head pain was the fifth leading cause of ED visits overall in the US and accounted for 1.2% of outpatient visits. The burden of headache was highest in females 18‐44, where the 3‐month prevalence of migraine or severe headache was 26.1% and head pain was the third leading cause of ED visits. The prevalence and burden of headache was substantial even in the least affected subgroup of males 75 or older, where 4.6% reported experiencing severe headache or migraine in the previous 3 months. Triptans accounted for almost 80% of antimigraine analgesics prescribed at office visits in 2009, nearly half of which were for sumatriptan. Migraine is associated with increased risk for other physical and psychiatric comorbidities, and this risk increases with headache frequency. Conclusion This report provides the most current available estimates of the prevalence, impact, and treatment patterns of migraine or severe headache in the United States. Migraine and other severe headaches are a common and major public health problem, particularly among reproductive‐aged women. Data about prevalence and disability from the major government‐funded surveillance studies are generally consistent with results of studies such as the American Migraine Studies 1 and 2, and the AMPP study.